The impact of adoption of conservation agriculture on smallholder farmers’ food security in semi-arid zones of southern Africa - Mango, Nelson; Siziba, Shephard; Makate, Clifton (Springer, 2017)
BACKGROUND In southern Africa, conservation agriculture (CA) has received a lot of research and promotional support from various organizations in the past decades. Conservation agriculture is largely promoted as one of the few win–win technologies affordable to farmers, in the sense that potentially it improves farmers’ yields (in the long term) at the same time conserving the environment. This is because conservation agriculture reduces nitrogen loss in the soil, promotes water and soil conservation and improves agronomic use efficiency of applied nutrients. However, some concerns have been raised over the feasibility of conservation agriculture on smallholder farms given constraints imposed by the biophysical and institutional realities under which smallholder farmers operate. The main aim of this study is to answer the question whether conservation agriculture is resulting in tangible livelihood outcomes to smallholder farmers. The counterfactual outcome approach was used to estimate ex post impact of conservation agriculture adoption on one of the key livelihood outcomes—food security. RESULTS The study that utilized a data set covering 1623 households in Zimbabwe, Malawi and Mozambique found no significant impact of conservation agriculture adoption on Food Consumption Score of farmers in Zimbabwe and Malawi. Possible reasons for the insignificant of CA impact on food security in Zimbabwe and Malawi could include the small land areas currently devoted to CA, and the failure to implement the full complement of practices necessary to set off the biophysical process that are expected to drive yield increases. In Mozambique, conservation agriculture significantly improved the Food Consumption Score for farmers exposed to the technology. A possible reason for effectiveness of CA in Mozambique could be due to the fact that often CA is being promoted together with other better cropping management practices such as timely weeding and improved seed varieties, which are poorly practiced by the generality of farmers in a country just emerging from a war period. CONCLUSION This paper provides one of the few ex post assessments of the impact of conservation agriculture adoption on household livelihood outcomes—food security. Given the mixed findings, the study suggests that conservation agriculture farmers in the three countries need to be supported to adopt a value chain approach to conservation agriculture. This entails the introduction of commercial or high-value crops in the conservation agriculture programmes, value addition on farmers produce, access to the necessary support services such as markets for seed, fertilizer, herbicides and equipment as well as reliable extension. We believe that under such circumstances conservation agriculture can effectively reduce food insecurity and poverty in the medium to long term.